LAS TORTUGAS CHELIDAE DEL TERCIARIO SUPERIOR Y CUATERNARIO DEL TERRITORIO ARGENTINO (Ameghiniana, 2013)
Remains of chelid turtles from the Late Miocene, Pliocene and Pleistocene of Argentina were analyzed. The specimens studied were referred to genera with living species. The first extinct species referred to the genus Acanthochelys is described. This new species is most closely realated to A. radiolata. The chelid turtles from the Upper Tertiary of northwestem and northeastem argentina (Parahydraspis paranensis included) are members of the supraspecific complex P. geoffroanus. The record of Hydromedusa cf. H. tectifera in the Early and Middle Pliocene and Late Pleistocene of Buenos Aires province is confirmed. The taxa Platemys laevis Ameghino, 1882, P. fossilis Ameghino,1882, P. antiqua Ameghino, 1882, P. robusta Ameghino 1882, are considered nomina nuda and ? Hydraspis arenarius nomen dubium, The chelid turtle dispersion during the Upper Tertiary in westem Argentina is related to the development of the sedimentary cycle named "Age of the southem plains".